Underground Cable Fault Analysis System Using Arduino with Bluetooth Controller - Sujatha Kesavan; Dr. V. S. Srinivasan (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Underground cable systems are widely utilized in urban areas for their aesthetic and safety advantages. However, detecting and locating faults in these cables presents a significant challenge due to the difficulty of pinpointing the exact fault location underground. This project aims to address this issue by developing a fault analysis system using an Arduino-based programmable circuit board combined with a Bluetooth controller. The proposed system is designed to accurately determine the distance of a fault from a base station in kilometers. By leveraging the Arduino board's capabilities and integrating a Bluetooth module for wireless communication, the system enables real-time fault detection and location tracking. This approach simplifies the repair process by providing precise fault location information, thereby enhancing the efficiency of maintenance operations and minimizing downtime. The proposed system represents a significant advancement in underground cable fault management, offering a practical and effective solution for improving infrastructure reliability.
Keywords: Underground Cable System; Fault Analysis; Arduino, Bluetooth Controller; Fault Detection; Distance Measurement; Infrastructure Maintenance; Real-time Tracking; Programmable Circuit Board